Relationship satisfaction and metabolic health parameters: a cross-sectional study in Burkinabe population of older adults - Adi Lukas Kurniawan; Julius Schretzmann; Rathi Paramastri; Alyssa Cho; Ali Sié; Melanie S. Fischer; Till Bärnighausen; Beate Ditzen (BMC, 2024)
Abstract Background Over- and undernutrition coexist in many African countries and pose a threat to metabolic health. This study assessed the associations between relationship satisfaction and Body Mass Index (BMI), waist circumference (WC), and glycated hemoglobin (HbA1c), in a rural population of older adults in Burkina Faso. It also explored potential gender differences and the mediating role of depressive symptoms. Methods Data from the "Centre de Recherche en Santé de Nouna (CRSN) Heidelberg Aging Study (CHAS)," a cross-sectional population-based study conducted in 2018 in Burkina Faso, were used in our study. Hierarchical linear regression models were applied for each of the three outcome variables. Among 2291 participants aged 40 years or older who provided data on relationship satisfaction, 2221, 2223, and 2145 participants had BMI, waist circumference (WC), and HbA1c values respectively. Results Higher relationship satisfaction (CSI-4 score) was associated with increased BMI (β = 0.05, p = 0.031) and WC (β = 0.12, p = 0.039). However, the association of CSI-4 and BMI became non-significant after controlling for depressive symptoms (PHQ-9 score) and physical inactivity (BMI: β = 0.04, p = 0.073). Depressive symptoms fully mediated the relationship between relationship satisfaction and BMI (β = -0.07, p = 0.005). There was no significant association between relationship satisfaction and HbA1c. These results were consistent across genders and age groups. Conclusion Higher relationship satisfaction may lead to increased body weight among Burkinabe adults aged 40 years and older, and depressive symptoms may be a mediator in this association.